The Use of Person-Centered Language in Scientific Research Articles Focused on Psychosis - Zach Monahan; Tanner Stone; Vinay Swami; Kelly Dunn; Micah Hartwell (Journal of Patient-Centered Research and Reviews)
Purpose: Societal stigma of psychosis leads to delayed treatment for individuals experiencing early symptoms, for fear of being labeled “crazy” or “psychotic.” Delayed treatment can worsen the prognosis of individuals with psychosis. Proper adherence to person-centered language (PCL) guidelines can curb the widely held stigmatized preconceptions about psychotic conditions.